An Empirical Study of OpenMP Directive Usage in Open-Source Projects on GitHub - Quevedo, Cristian Carvalho; Cavalheiro, Simone André da Costa; Oliveira Jr., Marcos Antonio de; Du Bois, André Rauber; Cavalheiro, Gerson Geraldo H. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2024: Anais do XXV Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad.2024.244777, 2024)
This paper presents a mapping of OpenMP API usage in open-source C/C++ projects on GitHub. The study investigates the frequency and patterns of OpenMP directive utilization through a data mining process on relevant repositories. The analysis reveals a predominant focus on loop parallelization and identifies opportunities for optimization in scheduling strategies and critical section handling. The study also uncovers underutilization of vectorization capabilities and potential for code restructuring to enhance parallel performance. The findings offer valuable insights into the practical application of OpenMP, contributing to the development of improved programming practices, educational resources, and tools that support efficient parallel programming with OpenMP. All software artifacts developed for this study are available to foster reproducibility and further research.